Canadian Cardiovascular Society and Canadian Thoracic Society Position Statement on Pulmonary Arterial Hypertension. Issue 6 (3rd September 2005) - Langleben, David; Archer, Stephen; Granton, John; Hirsch, Andrew M; Levy, Robert D; Mehta, Sanjay; Michelakis, Evangelos; Stewart, Duncan J
Abstract : The Canadian Cardiovascular Society and the Canadian Thoracic Society requested a position statement on pulmonary arterial hypertension from leading Canadian experts. The present document is intended to act as an update for the clinician, to provide a template for the initial evaluation of patients, to enable the understanding of current therapeutic paradigms based on approved indications for Canada, to highlight new therapies on the horizon, and to state the positions of the Canadian Cardiovascular Society and the Canadian Thoracic Society on resource management for pulmonary arterial hypertension in Canada.